Advances in Tumor Antigen‐Based Anticancer Immunotherapy: Recent Progress, Prevailing Challenges, and Future Perspective. Issue 2 (8th December 2022) - Shi, Wei; Chen, Shuang; Chi, Fanglian; Qiu, Qianqian; Zhong, Yue; Bian, Xiaojian; Zhang, Hao; Xi, Junting; Qian, Hai
Abstract: Elimination of tumors by regulating the immune system is the primary research focus in the rapidly developing field of immune‐oncology. Current immunotherapeutic strategies mainly include immune checkpoint blockade therapy, adoptive immune cell therapy, and cancer vaccines. Among them, tumor antigen‐based cancer vaccines can potentially elicit specific and potent anti‐tumor immune responses with less toxicity and side effects, which are recognized as promising treatments in immunotherapy. The selection of tumor antigens is the primary determinant of cancer vaccine design, whereas systematic reviews based on them are scarce. In the present review, currently known tumor antigens and recent developments in cancer vaccines based on tumor antigens, including traditional antigen vaccines, neoantigen vaccines, shared antigen vaccines, and oral antigen vaccines, in hopes of providing fundamental basis for further development of novel cancer vaccine‐based therapies, are summarized. Abstract : This review focuses on recent developments in currently known tumor antigens and tumor antigen‐based cancer vaccines, including traditional antigen vaccines, neoantigen vaccines, shared antigen vaccines, and oral antigen vaccines, with the hope of providing reference for cancer prevention and treatment and basis for the development of cancer vaccine‐based therapies.